URP-Based Shell Volumetric Fur Rendering with Multi-Layer Transparency and Ambient Occlusion: Optimization and Style Adaptation for Real-Time Game Graphics - Yilihamujiang, Yimier (European Journal of AI, Computing & Informatics, 2026)
This research article explores the optimization and style adaptation of URP-based shell volumetric fur rendering, enhanced with multi-layer transparency and ambient occlusion, for real-time game graphics. We investigate the performance implications of various parameters within the Universal Render Pipeline (URP) when rendering complex fur structures using a shell-based volumetric approach. The study focuses on implementing and optimizing multi-layer transparency to simulate the depth and density of fur, as well as integrating ambient occlusion to enhance the realism of light interaction within the fur volume. Furthermore, we explore methods for adapting the fur’s appearance to different artistic styles, considering aspects like color palettes, density variations, and geometric shaping. Our methodology involves a combination of shader development, performance profiling, and subjective visual evaluation. We analyze the impact of shell count, texture resolution, and transparency levels on rendering time, frame rates, and overall visual quality. Through iterative refinement and optimization, we aim to provide practical guidelines for achieving high-quality fur rendering in real-time game environments while maintaining artistic flexibility. The findings contribute to the advancement of efficient and visually appealing fur rendering techniques in game development, offering a balance between performance and aesthetic control. The developed techniques are evaluated in a test scene using Unity’s URP, demonstrating significant performance improvements and stylistic adaptability compared to naive implementations. This research provides insights into the challenges and opportunities of fur rendering in real-time applications, paving the way for more immersive and visually compelling game experiences.